Improved Genetic Transformation of Cork Oak (Quercus suber L.) - Álvarez-Fernández, Rubén; Ordás, Ricardo-Javier (Plant Cell Culture Protocols SE - 28, 2012)
An Agrobacterium-mediated transformation system for selected mature Quercus suber L. trees has been established. Leaf-derived somatic embryos in an early stage of development are inoculated with an AGL1 strain harboring a kanamycin-selectable plasmid carrying the gene of interest. The transformed embryos are induced to germinate and the plantlets transferred to soil. This protocol, from adult cork oak to transformed plantlet, can be completed in about one and a half years. Transformation efficiencies (i.e., percentage of inoculated explants that yield independent transgenic embryogenic lines) vary depending on the cork oak genotype, reaching up to 43%.
The following values have no corresponding Zotero field: periodical: Plant Cell Culture Protocols SE - 28 electronic-resource-num: 10.1007/978-1-61779-818-4_28
Keywords: AGL1; Agrobacterium tumefaciens; Cork oak; Fagaceae; Herbicide Resistance; kanamycin resistance; Quercus suber; Somatic embryogenesis; Tree genetic transformation